Pengaruh Social Media, Shopping Lifestyle, Dan Customer Experience Terhadap Perilaku Impulse Buying Gen Z Melalui E-Commerce - Suci Yulia Amanda; Figo Alimbel; Miftakhus Surur (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Expanding the limitations of the study to confirm the antecedents' influence on impulse buying, particularly in marketplace sales, is the expected contribution of this study. Thus, the study aims to examine the influence of shopping lifestyle, social media marketing, and customer experience on Gen Z's impulse buying in purchases through marketplaces. To do so, the study utilizes a quantitative design involving 110 samples selected through purposive sampling technique, where data are collected via questionnaires distributed to Gen Z individuals aged 17-25 years. Respondents' responses are analyzed through descriptive analysis and statistical analysis using SEM WarpPLS. The results of the analysis indicate that social media marketing and customer experience positively influence impulse buying, while shopping lifestyle is not confirmed to have a positive influence on impulse buying. The implications of this study underscore the necessity for companies to develop their strategies, particularly in boosting current sales by fostering social media activities, promotions, and enhancing customer experiences to drive purchases.